The influence of parenteral influenza vaccination on local immunity indices and microbiota of oropharyngeal secretion in patients with chronic inflammatory diseases of the upper respiratory tract - Zabolotny, D.I.; Melnikov , O.F.; Timchenko , S.V.; Sambur , M.B.; Rylska , O.G.; Volosevich, L.I.; Zayets, T.A.; Timchenko , M.D.; Faraon, I.V. (Medicni Perspektivi, 2021)
When studying the effect of vaccines against influenza, attention is mainly paid to obtaining high titers of protective antibodies in the blood and reducing the incidence of respiratory infections among vaccinated people. At the same time, the changes occurring in patient,s body from the factors of local specific and innate immunity remain insufficiently studied. The aim of the study was to determine the effect of parenteral influenza vaccination on the state of local immunity, cytology and microbiota of oropharyngeal secretion (OS) in patients with chronic inflammatory diseases of the upper respiratory tract. The study of immunological and microbiological parameters was performed in 32 patients with chronic inflammatory diseases of the upper respiratory tract, including 11 diagnosed with chronic rhinosinusitis, 9 – with chronic tonsillitis, 12 – with chronic pharyngitis, 3 and 12 weeks after vaccination with trivalent inactivated influenza-vaccine (PASTEUR, SA, France), which was administered intramuscularly. Single vaccination against influenza A and B has been shown to normalize reduced local humoral immunity indices, in particular sIgA and immune complexes concentrations, increase lymphocyte output to oropharyngeal secretions and cause a significant decrease in the representation of OS transient microflora without affecting the overall level of bacterial contamination. In both periods after the vaccination the reduced content of interferon-α in the OS of patients with chronic inflammatory diseases of the upper respiratory tract did not change. The obtained data allow to recommend vaccination against influenza virus in the period up to 3 months before the the beginning of mass infections as an effective means of stimulating the protective reactions of local immunity of oropharynx and nasopharynx mucous membranes in patients with chronic inflammatory diseases of the upper respiratory tract.